Pengetahuan Tradisional Masyarakat Papua dalam Mengenali, Mengklasifikasi dan Memanfaatkan Pandan Buah Merah (Pandanus conoideus Lam.) - Lisye I. Zebua; Eko B. Walujo (Jurusan Biologi FMIPA Universitas Cenderawasih, 2016)
Study on traditional knowledge of Papua communities for recognizing, classifying, and utilizing the Red fruit Pandanus cultivar (Pandanusconoideus Lam.) have been carried out in four Papua regions (Arfak-Manokwari mountain, Serui, Cyclops-Jayapura mountain, and Jayawijaya District). Sampling method of research was interview and observation methods. Informans were selected using purposive sampling and snowball sampling techniques. The data were analyzed on descriptive bases. The result showed that Papua communities have different knowledge of recognizing and managing the red fruit pandan. Characteristics used to distinguish cultivars were fruit size, seed size, and fruit colors. Based on ethno-biological data, there were two classification patterns of the red fruit in Papua. The first pattern were kingdom, life form, and specific structures. The second pattern were kingdom, life form, generic, and specific structures. The second pattern was similar to the botanical nomenclature. Utilization of the red fruit pandanwere morediverse in Papua communities living in mountainous than oher places, due to three important functions three functions, namely social, health, and economic functions. Utilization of the red fruit in Papua communities living in the bay areas were less varied, because the red fruit pandanwas only utilized as a food supplement. Generally, Papua communities living in the bay consumed the red fruit without being processed first.Key words: Classification, nomenclature, knowledgement, recognize, utilization.